Self-talk of junior figure skaters during a routine in competition - Piiroinen, Tommi (2022)
Self-talk belongs to one of the most used sport psychological skills to enhance performance and athletes have reported that self-talk influences one’s performance ability. Self-talk research in sports is traditionally concentrated on specific parts of self-talk and has been examined using laboratory interventions, thus, applicability to real-life competition environments is questionable. In addition, there is a lack of research considering aesthetic sport competition situations that are judged according to the third party. Figure skating is a sport which holds a long performance time, up to 4 minutes and 10 seconds, compared to many other sports where an athlete pace oneself to perform by taking several tries, shifts or performance itself is not constant considering the match time in ball games. Each second of figure skater’s performance affects scoring and this aspect creates a unique demand for athletes in aesthetic, ongoing performance sports: There cannot be any visible sign of preparation, including self-talk, to perform without lowering own performance scores. For this reason, it is important to investigate how athletes in figure skating are conducting themselves in competition situations. The aim of this study was to examine what type of self-talk figure skaters are using and how they are using it while performing their free skating program (3 minutes 30 seconds ± 10 seconds) during a competition. Data from three participants were gathered via semi-structured individual interviews, which was supported by self-report measurement that worked as a preliminary procedure and was answered immediately after performed routine. Video-footage of participants’ performance in competition was used during interviews to help them to reconstruct their self-talk as accurately as possible and to locate specifically the timing when self-talk emerged related to performed program elements. Transcribing the interviews generated 52 pages of data. Qualitative data were analysed using interpretative phenomenological analysis. The findings indicate that figure skaters’ self-talk was used in a reflexive manner during the performances at the competition. An instructional perspective as well as positive and negative valence characterized most of the skaters’ self-talk. Mind wandering existed, but to a lesser extent. Skaters were also worried about what others were thinking about them or their performances. The results of the study suggest that figure skaters were aiming to regulate and guide themselves during their performance in competition with self-talk, so forth, their performance level was not in automatic level. Even though the skaters’ self-talk was purely organic (spontaneous), it seemed to have a clear target (e.g., “Look at the judges!”) and function (e.g., earning more points) most of the time. Practical implications of the results include possibility to help athletes prepare for competition (acknowledge own self-talk and its’ effects) and enhance their performances (reflect and adjust self-talk according to situation) better. Future research directions include shifting from examining the content of self-talk to investigating the interpretation and functionality of athletes’ self-talk. To my knowledge, this is the first study that examines figure skaters’ self-talk during actual competitions.